Bystander Phage Therapy: Inducing Host-Associated Bacteria to Produce Antimicrobial Toxins against the Pathogen Using Phages - T. Scott Brady; Christopher P. Fajardo; Bryan D. Merrill; Jared A. Hilton; Kiel A. Graves; Dennis L. Eggett; Sandra Hope (MDPI AG, 2018)
Brevibacillus laterosporus is often present in beehives, including presence in hives infected with the causative agent of American Foulbrood (AFB), Paenibacillus larvae. In this work, 12 B. laterosporus bacteriophages induced bactericidal products in their host. Results demonstrate that P. larvae is susceptible to antimicrobials induced from field isolates of the bystander, B. laterosporus. Bystander antimicrobial activity was specific against the pathogen and not other bacterial species, indicating that the production was likely due to natural competition between the two bacteria. Three B. laterosporus phages were combined in a cocktail to treat AFB. Healthy hives treated with B. laterosporus phages experienced no difference in brood generation compared to control hives over 8 weeks. Phage presence in bee larvae after treatment rose to 60.8 ± 3.6% and dropped to 0 ± 0.8% after 72 h. In infected hives the recovery rate was 75% when treated, however AFB spores were not susceptible to the antimicrobials as evidenced by recurrence of AFB. We posit that the effectiveness of this treatment is due to the production of the bactericidal products of B. laterosporus when infected with phages resulting in bystander-killing of P. larvae. Bystander phage therapy may provide a new avenue for antibacterial production and treatment of disease.